Molecular characterization of human adenovirus associated with pediatric severe acute respiratory infections in a tertiary care hospital in North East India - Nath, Reema; Choudhury, Gargi; Gogoi, Arpita; Sarmah, Neelanjana; Bhattacharya, Neelakshi; Siddique, Aktarul Islam; Neog, Rahul; Dutta, Mousumi; Jakharia, Aniruddha; Borkakoty, Biswajyoti (Frontiers in Virology, 2024)
PurposeThe present study explored the molecular characterization of human Adenovirus (HAdV) and its strains among hospitalized SARI cases in the pediatric unit of a tertiary care hospital in North-East India.MethodsNasal and throat swabs were collected from 70 patients of Pediatric Unit, of a tertiary hospital in NE India from April 2023-October 2023. The samples were screened for the presence of HAdV using an adenovirus-specific Real-Time PCR Kit. For molecular characterization, Next Generation Sequencing (NGS) was performed by targeting the hexon gene of HAdV followed by post-sequencing analysis.ResultsOverall, 18.57% (13/70) of samples were positive for HAdV. In context of the severity of illness, 3/13 adenovirus-positive patients (23.07%) died after hospitalization, had severe pneumonia among which two were of less than one year of age. Molecular characterization using NGS indicated that 4/13 individuals were infected with HAdV-B type 3 and 5/13 patients were infected with HAdV type 7. Notably, 4/7 cases of severe pneumonia were under five years of age and associated with HAdV type 7 infection. The ratio of non-synonymous to synonymous mutation (dN/dS) was comparatively low in HAdV type 7 positive samples (dN/dS=0.31). No non-synonymous mutation was observed in HAdV-B type 3 positive samples. The higher neutrophil percentage among the death cases suggested an acute immune response.ConclusionThe study demonstrated HAdV type 7 and HAdV-B type 3 as strains associated with pediatric SARI cases from April 2023-October 2023. Further, HAdV type 7 infection was primarily linked with lower respiratory tract infections mainly severe pneumonia.